2020
DOI: 10.1101/2020.08.17.254193
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enhancers regulate 3′ end processing activity to control expression of alternative 3′UTR isoforms

Abstract: Enhancers are DNA elements that increase gene expression. mRNA production is determined by transcript production and polyadenylation site (PAS) cleavage activity. We established an assay to measure enhancer-dependent PAS cleavage activity in human cells because PAS cleavage may control alternative 3′UTR isoform expression. We found that enhancers are widespread regulators of PAS cleavage and consistently increase cleavage of proximal and weak PAS. Half of tested transcription factors exclusively regulated PAS … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 121 publications
(351 reference statements)
0
6
0
Order By: Relevance
“…In other cases, endogenous 3′UTR deletions led to the discovery of 3′UTR-dependent mRNA localization phenotypes (Terenzio et al, 2018). Although our data indicate that p53 abundance regulation is 3′UTR-independent, the 3′UTR may still have important functions possibly through control of protein localization or protein activity as has been shown for other proteins (Berkovits and Mayr, 2015;Moretti et al, 2015;Terenzio et al, 2018;Lee and Mayr, 2019;Mayr, 2019;Bae et al, 2020;Fernandes and Buchan, 2020;Kwon, 2020).…”
Section: Discussionmentioning
confidence: 49%
“…In other cases, endogenous 3′UTR deletions led to the discovery of 3′UTR-dependent mRNA localization phenotypes (Terenzio et al, 2018). Although our data indicate that p53 abundance regulation is 3′UTR-independent, the 3′UTR may still have important functions possibly through control of protein localization or protein activity as has been shown for other proteins (Berkovits and Mayr, 2015;Moretti et al, 2015;Terenzio et al, 2018;Lee and Mayr, 2019;Mayr, 2019;Bae et al, 2020;Fernandes and Buchan, 2020;Kwon, 2020).…”
Section: Discussionmentioning
confidence: 49%
“…Notably, a recent study that deleted 3′UTR sequences in several cytokine genes found similar discrepancies between reporter-based assays and gene expression from native contexts (Zhao et al, 2017). Although our data indicate that p53 abundance regulation is 3′UTR-independent, the 3′UTR may still have important functions possibly through control of protein localization or protein activity as has been shown for other proteins (Berkovits and Mayr, 2015; Moretti et al, 2015; Terenzio et al, 2018; Lee and Mayr, 2019; Fernandes and Buchan, 2020; Bae et al, 2020; Kwon, 2020; Mayr, 2019).…”
Section: Discussionmentioning
confidence: 53%
“…Our observations support the recently established role of the coding region as major regulator of mRNA stability and translation 13,14 . Although our data indicate that p53 abundance regulation is 3’UTR-independent, the human p53 3’UTR may still have important functions possibly through control of protein localization or protein activity as has been shown for other proteins 9,15-17 .…”
Section: Mainmentioning
confidence: 52%
“…RBBP6 did not copurify with CPSF and was therefore expressed and purified separately. As a model pre-mRNA substrate, we used a 218-nt fragment of the SV40 pre-mRNA, which has been shown to be cleaved efficiently in vivo ( Ryner and Manley 1987 ; Kwon et al 2021 ). We omitted the PAP enzyme and ATP from the reactions to focus on the cleavage step of pre-mRNA 3′ end processing ( Fig.…”
Section: Resultsmentioning
confidence: 99%